A note on multiple summing operators and applications. Issue 4 (3rd April 2019) - Albuquerque, N.; Araújo, G.; Pellegrino, D.; Rueda, P.
ABSTRACT: We prove a new result on multiple summing operators and, among other results and applications, we provide a new extension of Littlewood's 4 / 3 inequality to m -linear forms.